New Targets and Strategies for Rheumatoid Arthritis: From Signal Transduction to Epigenetic Aspect - Menglin Zhu; Qian Ding; Zhongxiao Lin; Rong Fu; Fuyuan Zhang; Zhaoyi Li; Mei Zhang; Yizhun Zhu (Biomolecules, 2023)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that can lead to joint damage and even permanent disability, seriously affecting patients’ quality of life. At present, the complete cure for RA is not achievable, only to relieve the symptoms to reduce the pain of patients. Factors such as environment, genes, and sex can induce RA. Presently, non-steroidal anti-inflammatory drugs, DRMADs, and glucocorticoids are commonly used in treating RA. In recent years, some biological agents have also been applied in clinical practice, but most have side effects. Therefore, finding new mechanisms and targets for treating RA is necessary. This review summarizes some potential targets discovered from the perspective of epigenetics and RA mechanisms.